Reduction of free fatty acid of waste vegetable oil by solid metal oxide catalysts - Chong, Bi Ling. (2009)
In order to reduce the world’s reliance on fossil fuels for petroleum-based fuel and to minimize pollution issues caused by fuels combustion, extensive research is conducted on biodiesel (fatty acid alkyl esters) synthesis. In this study, strong solid acid WO3/ZrO2 catalyst prepared via incipient wetness impregnation technique has proved to be an efficient catalyst for heterogeneous acid-catalyzed esterification of oleic acid with methanol. Reaction parameters that affect methyl oleate yields such as reaction time, calcination temperature, tungsten oxide loading, molar ratio of oleic acid to methanol and reaction temperature were compared. Zirconia support doped with various tungsten oxide composition of 5wt.%, 10wt.% 18wt.% and 28wt.% was calcined between 500oC and 900oC in order to achieve optimum calcination temperature. Catalytic activity was evaluated on molar ratio of oleic acid to methanol at a range of 1:2.5, 1:5 and 1:10. Additionally, performance of WO3/ZrO2 catalyst was further elaborated by varying reaction temperature from 80oC to 110oC at fixed molar ratio of 1:10. Optimization of reaction parameters with the most active 5wt.%WO3/ZrO2 catalyst calcined at 700oC showed that at 100oC and 1:2.5 oleic acid to methanol molar ratio, a maximum ester yield of 89.3% could be obtained over 8 hrs. The results illustrated the feasibility of this catalyst to convert oleic acid efficiently to methyl oleate at an activity of 4.39mmol oleic acid reacted/hr. g-cat. One drawback on this catalyst is that efficiency is reduced substantially by the presence of water.